2017
DOI: 10.18052/www.scipress.com/ijet.11.13
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Stress and Deformation Analysis of Curved Beams under Large Deflection

Abstract: Abstract. The paper presents a review on large deflection behavior of curved beams, as manifested through the responses under static loading. The term large deflection behavior refers to the inherent nonlinearity present in the analysis of such beam system response. The analysis leads to the field of geometric nonlinearity, in which equation of equilibrium is generally written in deformed configuration. Hence, the domain of large deflection analysis treats beam of any initial configuration as curved beam. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…7 The present work addresses three major research areas, namely, large static deformation, free vibration, and forced vibration of curved beams. Foundation theories for large static deformation analysis of curved beams along with several analysis methods are well documented in the papers, 8,9 and hence are not discussed here to maintain brevity. The foundation of large amplitude vibration of generalized beams along with several aspects of forced vibration characteristics of curved beams together with frequently encountered complicating effects due to non-classical parameters are discussed in the following paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…7 The present work addresses three major research areas, namely, large static deformation, free vibration, and forced vibration of curved beams. Foundation theories for large static deformation analysis of curved beams along with several analysis methods are well documented in the papers, 8,9 and hence are not discussed here to maintain brevity. The foundation of large amplitude vibration of generalized beams along with several aspects of forced vibration characteristics of curved beams together with frequently encountered complicating effects due to non-classical parameters are discussed in the following paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…31,33,34 As detailed review on such research works is out of scope of the present paper, interested readers may refer to the papers. 35,36…”
Section: Introductionmentioning
confidence: 99%
“…As focus of the present work is on loaded vibration of large statically deformed curved beam, scope of the present literature review includes two different aspects: large deflection analysis of curved beam under static loading and free vibration problem of such beams. Detailed review of static large deflection curved beam problem is previously reported in the review paper, 7 and hence, only the second aspects of the problem are presented here to maintain brevity.…”
Section: Introductionmentioning
confidence: 99%